CEO Pay-Performance Sensitivity: A Multi-Equation Model - Abraham, Rebecca; Harris, Judith; Auerbach, Joel (Scientific Research, 2014)
This study examines the variables influencing CEO compensation in the technology sector using both exclusively exogenous and interchangeably exogenous and endogenous variables. The study was confined to a single industry to isolate industry compensation practices which may be smoothed out in multi-industry studies. Multiple equations in a vector autoregressive model were used to explain compensation in recognition of the endogeneity of variables such as sales growth, stock returns and net income. Using US firms listed on the NASDAQ, we find that CEO compensation (measured separately as salary only, stock option grants only and total compensation from all sources) to be significantly explained by firm size, the ability to reduce debt, the ability to fund growth, net income and personal characteristics. CEOs are rewarded for achieving profitability. While there is an expectation of innovation in the technology sector with research and development expenditure increasing both sales and stock returns, such innovation only contributes to CEO compensation if it is translated into rising net income in an environment of debt-reduction. Further, CEOs are rewarded for implementing disruptive technology as a competitive strategy. The ability to fund growth is pertinent for the technology sector which may be restricted in its access to debt. Increases in age, tenure and the existence of celebrity status of the CEO led to increased compensation underscoring the importance of personal characteristics.
Keywords: CEO Compensation; Pay-Performance Sensitivity; Technology; Multi-Equation; Accounting Measures